2015
DOI: 10.1039/c4cp04124k
|View full text |Cite
|
Sign up to set email alerts
|

Electron migration behavior of Au/Cu multilayer films on Si substrates under UV radiation

Abstract: Au/Cu multilayer films were plated by the magnetron sputtering method on p-Si(100) substrates. The sample temperature was changed from room temperature to 44 °C under UV radiation in a vacuum within 120 minutes, and then remained stable with treatment time increased. Meanwhile, the surface roughness was changed from 4.2 nm to 5.9 nm and then also remained stable. But the interface width of Au/Cu still continued to increase during that steady stage. The calculation results show that the concentration gradient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…One could also expect the movement of Yb atoms in such a cathode unit as the work function of Yb (2.60 eV) is significantly lower than that of Mg (3.66 eV) (see Table 1 ). 26 However, the Yb atom has a larger atomic radius and higher atomic weight than either Mg or Ag atoms ( Table 1 ), which inhibits the migration of atoms, as discussed by Y. Cui et al 27 Hence, through these observations, we can confirm the UV stability of the cathode unit with a Yb : LiF EIL. On comparing the results before and after UV irradiation, almost negligible changes in the cathode unit are observed in Device B.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…One could also expect the movement of Yb atoms in such a cathode unit as the work function of Yb (2.60 eV) is significantly lower than that of Mg (3.66 eV) (see Table 1 ). 26 However, the Yb atom has a larger atomic radius and higher atomic weight than either Mg or Ag atoms ( Table 1 ), which inhibits the migration of atoms, as discussed by Y. Cui et al 27 Hence, through these observations, we can confirm the UV stability of the cathode unit with a Yb : LiF EIL. On comparing the results before and after UV irradiation, almost negligible changes in the cathode unit are observed in Device B.…”
Section: Resultsmentioning
confidence: 54%
“… 17 Earlier, Kai Yan et al reported that metals with a smaller work function are more likely to migrate to the surface layer relative to metals with a higher work function by UV radiation (a low pressure mercury lamp with a power of 7 W and wavelength of 245 nm) due to the increase in defects in the grain boundaries. 26 Also, Yun Cui et al showed that small metal ions easily diffused into the coating from the substrate, whereas larger metal ions had more difficulty doing so because of their large atomic radii. 27 Consequently, our subsequent investigation was focused on searching for an EIL which has excellent stability against UV irradiation and acceptable injection properties.…”
Section: Resultsmentioning
confidence: 99%
“…Because the effective radius of Al 3+ ion (0.039 nm) is larger than that of Si 4+ ion (0.026 nm), Al 3+ ions need higher activation energy for diffusion than Si 4+ ions. , Nonetheless, in the case of DUV irradiation, which can produce a moderate number of defects such as oxygen vacancies, the diffusion of metal ions can be substantially promoted. Indeed, this phenomenon could be more prominent with metal ions with relatively low work functions such as Al (4.06–4.26 eV) compared with Si (4.60–4.85 eV), as reported in the previous studies. Therefore, we suppose that despite the low-temperature (150 °C) condition, a thicker AlSiO x interlayer can be formed efficiently by DUV-assisted metal ion diffusion into the silicate layer (see also Figure f) and efficient thermal conduction through the underlying silicon substrate.…”
Section: Results and Discussionmentioning
confidence: 99%
“…8,15 Our previous study shows that UV radiation in a vacuum can induce the formation of defects and change the interface structures in Au/Cu metallic films, which damages the original designed structures and causes the final failure of the films. 16 Meanwhile, the size of electronic components decreases with the increasing severity of service conditions, for example, increasing current densities and therefore higher local temperatures. 17 Therefore, thin films and multilayered systems are subject to the risk of undergoing severe interdiffusion phenomena, which will result in the damage of the original surface, interface structure and material properties.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] In addition, advanced surface analysis tools, such as Auger electron spectroscopy (AES) and resolution transmission electron microscopy (HRTEM), can provide valuable information about structural differences at the interfaces and details of the atomic layer structures. 16,[28][29][30][31] In this study, we use a model sample, Au/Cu/Si(100), and mainly investigate the defect formation at the heterointerfaces and the evolution of interface structure induced by DC in a vacuum UV environment using AES and HRTEM.…”
Section: Introductionmentioning
confidence: 99%